Green crimes and dirty money - Spapens, A. C. (Green criminology, 2018)
Introduction / Toine Spapens, Rob White, Daan van Uhm and Wim Huisman -- Systemic drivers of green crimes -- Destruction and the philosophy of desire / Vincenzo Ruggiero -- Environment, conflict and profit : harmful resource exploitation and questionable revenue generation / Avi Brisman and Nigel South -- Eco-mafia and environmental crime in Italy : evidence from the organised trafficking of waste / Anna Rita Germani, Antonio Pergolizzi and Filippo Reganati -- Supply and demand : regulation and the trade in illegal wildlife / Amy Couper and Reece Walters -- Corporations, environmental violations and the money -- The "dieselgate" scandal : a criminological perspective / Toine Spapens -- Environmental responsibility and firm value / Nadja Guenster and Jakob Koegst -- Too big to deter, too small to change? profitability and environmental compliance in the waste and chemical industry in the Netherlands / Karin van Wingerde and Marieke Kluin -- Waste crime from three criminological perspectives : implications for crime control and harm prevention / Lieselot Bisschop and Wim Huisman -- Financial regulation and enforcement -- Green with envy : environmental crimes and black money / Michael Levi -- Wildlife and laundering : interaction between the under and upper world / Daan van Uhm -- The limits of ecological modernisation to effectively manage greenhouse gas emissions : a case study of carbon market crime / Ruth McKie -- Financial investigation in environmental crime cases in the Netherlands / Rudie Neve and Nanina van Zanden -- Sentencing environmental offenders : it is not just about the money / Rob White -- Index